Electromagnetic organ tracking allows for real-time compensation of tissue shift in image-guided laparoscopic rectal surgery: results of a phantom study - Wagner, Martin; Gondan, M.; Zöllner, C; Vetter, Josephin; Nickel, Felix; Albala, Lorenzo; Groch, A; Suwelack, S.; Speidel, Stefanie; Maier-Hein, Lena; Müller, Beat P.; Kenngott, Hannes Götz (Surgical endoscopy and other interventional techniques, 2016)
Laparoscopic resection is a minimally invasive treatment option for rectal cancer but requires highly experienced surgeons. Computer-aided technologies could help to improve safety and efficiency by visualizing risk structures during the procedure. The prerequisite for such an image guidance system is reliable intraoperative information on iatrogenic tissue shift. This could be achieved by intraoperative imaging, which is rarely available. Thus, the aim of the present study was to develop and validate a method for real-time deformation compensation using preoperative imaging and intraoperative electromagnetic tracking (EMT) of the rectum.
Published online: 23 June 2015
Gesehen am 05.06.2020